The Influence of Family Business Exposure on Succession Intention with Affective Commitment as a Mediator - Arani Puspa Negara; Metta Padmalia (Journal of Accounting and Finance Management, 2026)
Family businesses play a very important role in the Indonesian economy, but business sustainability still faces serious challenges, especially in the intergenerational succession process. This study aims to analyze the influence of family business exposure on succession intention, with affective commitment as a mediating variable. This study uses a quantitative approach with data collected thru online questionnaires distributed to students from entrepreneurial families. The data is analyzed to identify the relationships between the research variables. The research results indicate that the exposure of the next generation to family business activities is able to strengthen emotional attachment to the family company, which in turn increases the intention to continue family business leadership. Additionally, family business exposure also directly influences succession intention, with affective commitment acting as a partial mediator. This finding confirms the importance of successor generation involvement in family businesses accompanied by positive emotional relationships. This research recommends that family business owners actively involve the next generation in business activities and build supportive intergenerational relationships to improve succession success and business sustainability.